Approximation Practice on Students' Writing - Royana Mukorobin; Agus Widyantoro (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2018)
The primary aim of this paper is to investigate students’ difficulty in the implementation of genre-based approach to teach English skills. It focuses on approximation exercise. The author reported the result of the study in the form of qualitative data. The practice revealed that the students faced difficulty to start writing their ideas. In this point, the students who have quite good English proficiency felt easy in constructing the text without employing elementary sentences. It happens although their text construction is somehow not grammatically correct. On the other hand, for those who have low English proficiency, the incorporation of elementary sentences and final realization help them a lot in constructing the text effectively. In a nutshell, the students in high and low English proficiency have their own difficulty in putting their ideas in the form of a text. Teacher’s assistance is crucial in developing students’ skill independently. Finally, this pedagogical practice might become the teacher’s guidance in practicing genre-based approached in the classroom.